SOCIOECONOMIC DETERMINANTS OF CIRCULAR MIGRATION OF WORKERS: EMPIRICAL EVIDENCE FROM THE RETAIL INFORMAL SECTOR - Yaqinatul Muzayyana; Anna Zakiyah Hastriana (Nurul Jadid University, 2026)
Circular migration is a form of non-permanent labor mobility that is commonly carried out by rural communities in response to limited employment and inequality of welfare between regions. This phenomenon is especially prevalent in the urban informal sector, including small retailers such as grocery stores, which are relatively accessible to the workforce even with low educational backgrounds. This study aims to evaluate the influence of employment opportunities, wage rates, and family dependents on the circular migration of workers from Lenteng District, Sumenep Regency. The research applied a quantitative design using a survey of 100 respondents chosen through purposive sampling. Primary data were gathered via a five-point Likert-scale questionnaire and processed using multiple linear regression with SPSS. The findings indicate that employment opportunities, wage rates, and family dependents positively and significantly affect circular migration, both individually and collectively. These findings emphasize the importance of strengthening the rural economy and protecting the informal retail sector as an effort to mitigate welfare inequality between regions.